Effects of maternal exposure to phthalates and bisphenol A during pregnancy on gestational age. (March 2014) - Weinberger, Barry; Vetrano, Anna M.; Archer, Faith E.; Marcella, Stephen W.; Buckley, Brian; Wartenberg, Daniel; Robson, Mark G.; Klim, Jammie; Azhar, Sana; Cavin, Sarah; Wang, Lu; Rich, David Q.
Abstract Objective: Phthalates and bisphenol A (BPA) are ubiquitous environmental toxicants, present in high concentrations in numerous consumer products. We hypothesized that maternal exposure to phthalates and BPA in pregnancy is associated with shortened gestation. Methods : Urinary phthalate and BPA metabolites from 72 pregnant women were measured at the last obstetric clinic visit prior to delivery. Using linear regression models, we estimated the change in gestational age associated with each interquartile range (IQR) increase in phthalate and BPA metabolite concentration. Results: IQR increases in urinary mono(2-ethyl-5-hydroxyhexyl) phthalate (MEHHP) and BPA concentrations were associated with 4.2 and 1.1 d decreases in gestation, respectively. When stratified by gender, these alterations were found only in male infants. Conclusions: We conclude that MEHHP and BPA (free + glucuronide) are associated with reductions in gestation, with effects observed only in males. Our findings are consistent with the idea that these agents induce gender-specific alterations in signaling via PPAR-γ transcription factor, androgen precursors and/or inflammatory mediators during the initiation of labor.